If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -1x = -1(4 + 7x) 11 + -1x = (4 * -1 + 7x * -1) 11 + -1x = (-4 + -7x) Solving 11 + -1x = -4 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 11 + -1x + 7x = -4 + -7x + 7x Combine like terms: -1x + 7x = 6x 11 + 6x = -4 + -7x + 7x Combine like terms: -7x + 7x = 0 11 + 6x = -4 + 0 11 + 6x = -4 Add '-11' to each side of the equation. 11 + -11 + 6x = -4 + -11 Combine like terms: 11 + -11 = 0 0 + 6x = -4 + -11 6x = -4 + -11 Combine like terms: -4 + -11 = -15 6x = -15 Divide each side by '6'. x = -2.5 Simplifying x = -2.5
| 6x+2-3+4x=14-5x | | 7z+5=10(z-7)-3z | | 6x-2=2(x+1) | | 4x^2+4y^2+32x+28y+105=0 | | 5x^2-8-3=0 | | 2x+(1.5)=-3 | | X^3+8=9 | | -7(m+4)+6m=-m-26 | | sqrt(5x+3)=3sqrt(x) | | -6x+-4-(5x-4)= | | -1+8p=-2(-4p-2)-5 | | y=-x^2+10x-18 | | 2/3=18/s | | X=56000+.07X | | 16-7p=3(6-3p) | | 8h/200 | | 16-7p=3(7-3p) | | x+5+3x-7=90 | | v=(4)(6)(23) | | -r-15.8=24.6 | | 14s-28=4s+14 | | 7(3n-5)+25=11n | | Y+2x=-20 | | 2x+2y=20.523 | | 2x+(-2x-3)=-3 | | (7+3x)*3x=4x^2 | | 1.2h+3.3(2.4-h)=41 | | x^14/x^13 | | 14s-28=-7f-19 | | 101.7+10n+19n=180 | | 5x(x+6)-2x=3(x+10) | | 2.3h-4+1.2h=3.5 |